Предмет:
МатематикаАвтор:
andreas1u0dАвтор:
harleyszr6Автор:
yaretziОтвет:
4mn
Пошаговое объяснение:
(m + n)²- (m - n)² = ( m² + 2mn + n²) - (m² - 2mn + n²) = m² + 2mn + n² - m² + 2mn - n² = 2mn + 2mn = 4mn
Удачи)))
Автор:
charlizearellanom^2 + 2mn + n^2 - (m^2 - 2mn + n^2) = m^2 + 2mn + n^2 - m^2 + 2mn - n^2 = 4mn.
Не уверена в ответе.
Автор:
cumuluspj1hДобавить свой ответ
Предмет:
Русский языкАвтор:
tuckggsoОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
augustocooperОтветов:
Смотреть
Предмет:
Английский языкАвтор:
avery75Ответов:
Смотреть
Предмет:
Қазақ тiлiАвтор:
frankycrossОтветов:
Смотреть